Direct emissions of nitrous oxide from combustion of gaseous fuels. (5th January 2017) - Colorado, Andrés; McDonell, Vincent; Samuelsen, Scott
Abstract: After molecular nitrogen, nitrous oxide (N2 O) is the second most abundant nitrogen compound in the atmosphere and its concentration is rising at rate of 0.26% yr −1 (0.7 ppb yr −1 ). In the troposphere N2 O is a relatively stable compound, however it is reactive in the stratosphere, where it is destroyed by photolysis with ultraviolet radiation. While photolysis in the stratosphere removes this potent greenhouse gas from the atmosphere, subsequent reactions also destroy protective ozone. Hence N2 O is both a greenhouse gas and an ozone depleting gas and its increasing levels in the atmosphere warrant further understanding of its sources, including combustion. Most research on combustion generated N2 O has focused on emissions from solid and liquid fuels, since these fuels contain nitrogen bonded to their molecular structure (fuel-nitrogen). It has been shown that this fuel bound nitrogen can be oxidized into N2 O under relatively low temperature conditions. To date, direct emissions of N2 O from combustion of typical gaseous fuels (which have no fuel bound nitrogen) have not received attention due to the established link fuel nitrogen and N2 O emission. This paper presents evidence of alternative mechanisms of N2 O emissions that do not involve fuel bound nitrogen. Of particular interest are lean premixed flames widely used for current low NOx combustion systems. Measurements were made under different operational modes: Steady state, ignition, and lean blowoff. A variety of gaseous fuel mixtures without fuel nitrogen including natural gas were considered, including, biogas and natural gas with up to 70% H2 added (by volume). The results indicate that combustion of these fuels can directly emit significant levels of N2 O, in particular during transient events such as ignition and blowoff. Furthermore, steady state combustion of hydrogen enriched natural gas flames (which can be operated at very lean conditions due to the stabilizing effects of hydrogen), can also lead to the direct emissions of N2 O. Highlights: Direct emissions of nitrous oxide from a 117 kW boiler system are measured. Nitrous oxide emissions are found even for fuels that contain no nitrogen. Low combustion temperatures and transient events favor emission of nitrous oxide. Adding hydrogen to natural gas allows conditions favoring nitrous oxide emission. Different detailed kinetic mechanisms predict widely varying nitrous oxide behavior.